2021
DOI: 10.24018/ejmed.2021.3.4.844
|View full text |Cite
|
Sign up to set email alerts
|

Social Features and Morbidity Patterns of Women with Obstetric Fistulae at an Obstetric Fistula Centre in a University Teaching Hospital in Jos, Nigeria

Abstract: Obstetric fistulae are largely preventable surgical conditions. Literature has shown that it is common among the low income, less privileged and marginalized members of the community. It affects mainly the poor, young, illiterate girls, and women in the remote rural areas of the world, where access to emergency obstetric care, family planning services and skilled birth attendants are unavailable. And when available are poorly utilized due to cost, distance, and other challenges. This study seeks to identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Evidence shows that many women and girls with obstetric fistulas faced many psychological problems such as humiliation (reported by 97.2% of victims); abandonment, stigmatization, and loneliness (reported by 95.8%) [ 13 – 15 ]. Similar studies showed that 85% of women experienced separation from their husbands, and 95.4% reported despair [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence shows that many women and girls with obstetric fistulas faced many psychological problems such as humiliation (reported by 97.2% of victims); abandonment, stigmatization, and loneliness (reported by 95.8%) [ 13 – 15 ]. Similar studies showed that 85% of women experienced separation from their husbands, and 95.4% reported despair [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that many women and girls with obstetric fistulas faced many psychological problems such as humiliation (reported by 97.2% of victims); abandonment, stigmatization, and loneliness (reported by 95.8%) [13][14][15]. Similar studies showed that 85% of women experienced separation from their husbands, and 95.4% reported despair [15,16]. Women with obstetric fistulas are often afraid and uncertain about their future with sexual partners, marriage, sex, pregnancy, childbirth, and reintegration into the neighborhood community [17][18][19].…”
Section: Introductionmentioning
confidence: 99%